Non-linear Based Hybrid Denoising filter for Alzheimer’s disease Magnetic Resonance Imaging - Senthilnathan, R; Marimuthu, A (International Journal of Computer Sciences and Engineering, 2025)
Noise is a natural property of medical imaging, and it commonly tends to diminish the image resolution as well as contrast, thus dropping the diagnostic rate of this imaging modality, there is a developing attentiveness in using noise reduction techniques in a variety of medical imaging applications. This paper presents a hybrid nonlinear filtering algorithm in which the proposed method has two stages. In the first stage, the rank-ordered sequence is used to decide whether a pixel is corrupted or not based on a decision measure which considers the differences of adjacent pixel values in the input image. In the second stage, the replacement is done by the weighted median value of uncorrupted pixels in the filte1ing window. The visual and experimental results show that the proposed filter can provide very high quality restored images with image detail preservation for various level noise density images